A tungsten alloy with excellent armor-piercing performance and its preparation method and application

By adding silicon oxide and yttrium to the tungsten alloy, the problem that tungsten alloy is prone to produce a ‘mushroom head effect’ during the armor-piercing process is solved, and the excellent armor-piercing performance of tungsten alloy is achieved and its ability to penetrate the armor is enhanced.

CN118563191BActive Publication Date: 2025-02-07ZIGONG ZHONGXING WEAR-RESISTANT NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410823921.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-02-07
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

Tungsten alloys are prone to 'mushroom head effect' during the armor-piercing process, resulting in a reduced penetration ability and making it difficult to achieve excellent armor-piercing performance.

Method used

By adding silicon oxide and yttrium to the tungsten alloy, the silicon oxide is evenly distributed using a special addition process, changing the dynamic strain characteristics of the tungsten alloy, and improving its shear strain characteristics and 'self-sharpening' ability.

Benefits of technology

The armor-piercing performance of tungsten alloy is significantly improved, making it show excellent shear strain characteristics and brittle fracture characteristics during the armor-piercing process, and enhancing its ability to penetrate the armor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118563191B_ABST
    Figure CN118563191B_ABST
Patent Text Reader

Abstract

The invention discloses a tungsten alloy with excellent armor-piercing performance, a preparation method and an application thereof. The tungsten alloy is prepared from the following raw materials by mass percentage: 93% of W powder, 3-4.8% of Ni powder, 1-2% of Fe powder, 0.8-1.5% of Co powder, 0.3-1.0% of SiO2 powder, 0.1-0.3% of Y, and the remainder is inevitable impurities, which is 100% in total. The invention significantly improves the shear strain characteristics and self-sharpening ability of the material by adding silicon oxide + Y to the tungsten alloy, and at the same time, a special addition process is used to make silicon oxide evenly distributed in the tungsten alloy, so that tungsten grains and silicon oxide grains are adjacent to each other and bonded, thereby changing the dynamic strain characteristics of the tungsten alloy, improving the dynamic mechanical properties and adiabatic shear sensitivity of the alloy, and making the tungsten alloy have excellent armor-piercing performance as a whole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tungsten alloy preparation, and in particular to a tungsten alloy with excellent armor-piercing performance and a preparation method and application thereof. Background Art

[0002] High-density tungsten alloy is mainly composed of tungsten phase and bonding phase, in which the content of tungsten phase is between 85-97%, and the γ bonding phase is mainly composed of Fe, Ni, Cu and other elements. The main material systems are W-Ni-Fe, W-Ni-Cu and W-Hf. In general, the penetration ability of depleted uranium alloy core is about 10-15% higher than that of tungsten alloy core under the same conditions. The main difference between the two is that the critical adiabatic shear strain rate and critical adiabatic shear strain value of depleted uranium alloy material are low, and adiabatic shear fracture is easy to occur, with a "self-sharpening" effect, while the head of tungsten alloy core is "mushroom-shaped" under the action of axial penetration force, resulting in increased penetration resistance and reduced penetration ability. High-density tungsten alloy is prone to produce "mushroom head effect" during armor-piercing process, which weakens its armor-piercing power.

[0003] The penetration of armor-piercing projectiles into armor is a deformation and destruction process at a high strain rate. The core of the armor-piercing projectile is subjected to a large impact pressure (greater than 5GPa) in the interaction with the target plate, causing plastic deformation. Due to the extremely high speed during plastic deformation, the heat generated cannot be conducted out in time and is limited to a narrow area, causing the internal temperature of the metal to rise, causing the material to soften and the strength to decrease. When the degree of strength reduction caused by the temperature rise exceeds the strength increase caused by the deformation and strengthening of the material, an adiabatic shear band will be generated. Depleted uranium alloys have high adiabatic shear sensitivity, and adiabatic shear bands will be generated at low strain rates. Cracks extend along the shear bands, and the material at the edge of the core head is prone to collapse, which is equivalent to sharpening the warhead, which can keep a very small action area between the projectile and the target, reduce the penetration resistance and prolong the action time, and significantly increase the penetration depth.

[0004] For kinetic energy armor-piercing projectile materials, once the shape of the armor-piercing projectile is determined, there are two main factors to ensure that it has good armor-piercing performance: one is good mechanical properties, such as high strength, good toughness and plasticity, to ensure that the armor-piercing can be complete during launch and landing; the other is to have good "self-sharpening" ability, so that the material at the edge can peel off along the adiabatic shear band during the armor-piercing process to ensure the armor-piercing effect. Figure 1 As shown, Figure 1This is a schematic diagram of the armor-piercing process of depleted uranium alloy and tungsten alloy. Due to its high adiabatic shear band formation ability, depleted uranium alloy has high armor-piercing performance, while tungsten alloy is difficult to undergo adiabatic shear failure due to its strong strain rate sensitivity. It is easy to form mushroom heads during the armor-piercing process, which seriously reduces its armor-piercing performance. Therefore, how to improve the "self-sharpening" ability of tungsten alloy during the armor-piercing process, promote shear strain, and improve adiabatic shear sensitivity has become the core technology for improving the armor-piercing performance of tungsten alloy armor-piercing projectiles.

[0005] At present, the research direction in China is to use the addition of alloying elements in the preparation process of tungsten alloy to form a strengthening effect with the tungsten phase and the bonding phase components, such as solid solution strengthening, dispersion strengthening, and precipitation strengthening. By changing and optimizing the microstructure, the formation of adiabatic shear bands in tungsten alloys under dynamic loading conditions is promoted, and the self-sharpening effect is improved. For example, refractory metals such as Mo, Ta, and Nb are added to the alloy. Because these elements can be dissolved with the tungsten phase, the diffusion of tungsten to the bonding phase is reduced, and the growth of tungsten grains during sintering is effectively inhibited, thereby refining the grains and improving the strength performance. However, while improving the strength, it is also easy to make the tungsten alloy "hard and brittle", and the armor-piercing effect is limited. Another research direction is to add trace rare earth element oxides, such as adding CeO2, ZrO2, La2O3, ThO2, V2O3, etc. to disperse in the alloy to achieve dispersion strengthening and improve the strength and hardness of the alloy. However, the mechanical properties of the alloy are significantly reduced after addition, and the strength and elongation will also be significantly reduced.

[0006] Chinese patent CN111057926A discloses a tungsten alloy and a preparation method thereof. The expression of the tungsten alloy is W 100%-t Ni a X b Y c Z d, where X represents one or more of Fe, Cu, Cr, Co, and Mn, Y represents one or more of Al2O3, Y2O3, ZrO2, and SiO2, and Z represents one or more of TiC, Cr3C2, VC, and WC. a ranges from 0.2% to 4.0%, b ranges from 0.05% to 3.0%, c ranges from 0.05% to 2.0%, d ranges from 0.05% to 3.0%, and t is the sum of a, b, c, and d, and ranges from 1.5% to 5.5%. In this patent, the addition of Ni and X components is conducive to the formation of alloy structure, improves the bonding strength between the bonding phase and the tungsten matrix, and promotes the alloy structure to have a higher density, meeting the strength required for the launch and penetration of tungsten alloy materials when used as projectile cores. The Y component is conducive to the formation of hard and brittle metal oxide particles distributed in the alloy structure, which can effectively improve the compressive strength of tungsten alloy materials, improve the brittleness of tungsten alloys, and reduce the elongation of tungsten alloys. During the armor-piercing process of the projectile core, under the action of stress waves, microcracks first appear at the interface between these metal oxide particles and the bonding phase, and the crack expansion separates the interface, and finally forms a separation and fracture of the metal oxide particles and the bonding phase, resulting in the generation of a large number of fragments, thereby forming a large number of fragments, achieving a secondary damage effect, and the components can effectively refine the grains and form hard and brittle intermetallic compounds with the bonding phase, so that the hardness of the tungsten alloy material is increased, and the armor-piercing power of the tungsten alloy projectile core is improved. This patent does not improve the armor-piercing performance of tungsten alloy from the core perspective of improving the self-sharpening ability and adiabatic shear sensitivity of tungsten alloy, and its improvement of the armor-piercing performance of tungsten alloy is limited. Summary of the invention

[0007] The purpose of the present invention is to provide a tungsten alloy with excellent armor-piercing performance and its preparation method and application in view of the above-mentioned existing problems. The present invention significantly improves the shear strain characteristics and self-sharpening ability of the material by adding silicon oxide to the tungsten alloy, and at the same time uses a special addition process to make silicon oxide evenly distributed in the tungsten alloy, so that part of the tungsten grains in the tungsten alloy are separated from the bonding phase by silicon oxide, and the phenomenon of tungsten grains, silicon oxide grains and bonding adjacent to each other occurs, changing the dynamic strain characteristics of the tungsten alloy, avoiding the problem that the material produces large plastic deformation when subjected to force, and finally breaks. In addition, the present invention removes residual oxygen by adding Y, while playing the role of dispersion strengthening, reducing the oxygen content at the interface between the tungsten phase and the bonding phase, improving the dynamic mechanical properties and adiabatic shear sensitivity of the alloy, and making the tungsten alloy have excellent armor-piercing performance as a whole.

[0008] The technical solution adopted by the present invention is as follows: a tungsten alloy with excellent armor-piercing performance, which is prepared from the following raw materials by mass percentage: 93% W powder, 3-4.8% Ni powder, 1-2% Fe powder, 0.8-1.5% Co powder, 0.3-1.0% SiO2 powder, 0.1-0.3% Y, and the remainder is inevitable impurities, which totals 100%.

[0009] Furthermore, the particle size of the W powder is 1-2 μm, the particle size of the Fe powder is 2-5 μm, the particle size of the Co powder is 1-2 μm, and the particle size of the silicon dioxide powder is 2-5 μm.

[0010] Furthermore, the silicon dioxide powder is prepared from silicate powder; the raw material metal yttrium is provided by yttrium complex salt solution.

[0011] Furthermore, in the tungsten alloy, the SiO2 content is 0.5-1.0%, and the Y content is 0.3%.

[0012] Furthermore, in the tungsten alloy, the SiO2 content is 1.0% and the Y content is 0.3%.

[0013] Furthermore, the present invention also includes a method for preparing a tungsten alloy having excellent armor-piercing performance, comprising the following steps:

[0014] A. Preparation of mixed materials: Add W powder, Ni powder, Fe powder, Co powder and SiO2 powder into a ball mill, sieve after ball milling, and then filter and dry to obtain a rubber-doped material;

[0015] B. Mixing the rubber-doped material and the yttrium complex salt solution in a mixer, evacuating the mixer, injecting a protective gas into the mixer, and then rotating and mixing, and placing the mixture in a microwave-ultrasonic composite field for microwave-ultrasonic coordinated treatment, and discharging the mixture after the mixing is completed to obtain a primary mixture;

[0016] C. Pressing and sintering: the primary mixture is pressed and formed to obtain a sample blank, the sample blank is loaded into a molybdenum boat, and a one-time sintering is performed in a muffle furnace in a H2 atmosphere, and the obtained sample is sandblasted;

[0017] D. Vacuum tempering, hot rotary forging and multiple heat treatments. The sintered and sandblasted samples are placed in a vacuum furnace for high-temperature tempering and vacuum dehydrogenation. The samples are then hot rotary forged. The forged samples are subjected to multiple vacuum heat treatments. The heat treatment is repeated 3-4 times. The quenching temperature is gradually increased each time. No tempering is performed after quenching.

[0018] Furthermore, in step C, the sintering process is as follows: the sample dewaxing time is 3-4 hours, the sintering temperature is 1460-1500° C., and the high temperature sintering time is 1.5-2.0 hours.

[0019] Further, in step D, the high-temperature dehydrogenation and tempering temperature is 1100-1200°C, the holding time is 2h, and the vacuum degree is 0.05-0.1Pa; the hot rotary forging temperature is 900-1000°C, and it is carried out under the protection of N2 atmosphere, and the radial dimension deformation after rotary forging is 20-30%.

[0020] Further, in step D, the vacuum heat treatment process parameters are: vacuum degree of 5-10Pa, temperature of 1050-1300°C, insulation time of 1.5-2h, and water quenching.

[0021] Furthermore, the present invention also includes an application of a tungsten alloy with excellent armor-piercing performance in military equipment, wherein the tungsten alloy is used as a raw material for preparing armor-piercing projectiles, wherein the tungsten alloy is prepared by a preparation method.

[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0023] 1. The present invention provides a method of significantly improving the shear strain characteristics and "self-sharpening" ability of the material by adding silicon oxide and yttrium during the preparation process of tungsten alloy, so that the tungsten alloy has excellent armor-piercing performance. The present invention uses a special addition process to make silicon oxide evenly distributed in the tungsten alloy, so that part of the tungsten grains in the tungsten alloy are separated from the bonding phase by silicon oxide, and the tungsten grains, silicon oxide grains and bonding phases are adjacent to each other. When the tungsten alloy is subjected to stress deformation, in the early stress stage, the silicon oxide grains play a certain role in solid solution strengthening and dispersion strengthening, thereby improving the strength of the tungsten alloy. When the stress reaches a certain critical value, due to the silicon oxide Due to the presence of grains, silicon oxide grains partially separate the tungsten grains from the bonding phase, which sharply reduces the original bonding strength between the tungsten grains and the bonding phase, causing cracks to quickly form between the tungsten grains and the silicon oxide grains, and rapidly expand between the tungsten grains and the bonding phase and the silicon oxide grains; at the same time, due to the presence of silicon oxide grains in the bonding phase, when the stress reaches the critical point, there is no need for the bonding phase to produce a large strain, and cracks can be quickly generated between the silicon oxide grains and the bonding phase, and rapidly expand, and the material as a whole exhibits a strong shear strain characteristic, so that the material will not produce a large plastic deformation when subjected to stress and finally break;

[0024] 2. In addition to adding silicon oxide, the present invention also adds yttrium, which helps yttrium react with residual oxygen in the tungsten alloy to generate oxides during the sintering process, plays a role in dispersion strengthening, and reduces the oxygen content at the interface between the tungsten phase and the bonding phase, thereby improving the dynamic mechanical properties and adiabatic shear sensitivity of the tungsten alloy;

[0025] 3. While improving the alloy formula, the present invention cooperates with the multiple heat treatment processes proposed by the present invention to strengthen and stabilize the dissolution of silicon oxide, Y and W in the bonding phase, increase the strength of the bonding phase, so that the tungsten alloy has high strength and sensitive shear strain characteristics, that is, the material exhibits brittle fracture after a certain strain, so that the tungsten alloy has excellent armor-piercing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the armor penetration process of depleted uranium alloy and tungsten alloy;

[0027] Figure 2 This is a tensile strength test chart of a conventional high-strength and high-toughness 93W alloy sample;

[0028] Figure 3 The tensile strength test of the TA93W alloy sample of the present invention Figure 1 ;

[0029] Figure 4 Tensile strength test of TA93W alloy sample of the present invention Figure 2 ;

[0030] Figure 5 This is a tensile strength test diagram of a TB93W alloy sample of the present invention;

[0031] Figure 6 The tensile strength test of the TC93W alloy sample of the present invention Figure 1 ;

[0032] Figure 7 The tensile strength test of the TC93W alloy sample of the present invention Figure 2 ;

[0033] Figure 8 This is the metallographic diagram of a conventional high-strength and high-toughness 93W alloy sample;

[0034] Fig. 9 This is the backscattered electron image of a conventional high-strength and high-toughness 93W alloy sample;

[0035] Fig.10 is a metallographic diagram of a TA93W alloy sample of the present invention;

[0036] Fig.11 This is a backscattered electron image of the TA93W alloy sample of the present invention;

[0037] Fig.12 It is the metallographic diagram of the TB93W alloy sample of the present invention;

[0038] Fig.13 This is a backscattered electron image of the TB93W alloy sample of the present invention;

[0039] Fig.14 is a metallographic diagram of a TC93W alloy sample of the present invention;

[0040] Fig.15 This is a backscattered electron image of the TC93W alloy sample of the present invention;

[0041] Fig.16 This is a diagram showing the impact of the 8th steel plate (front and rear) of No. 1, 2, 3, and 4 bullets of the present invention;

[0042] Fig.17 It is a diagram showing the impact of the 8th steel plate and the first aluminum plate of the No. 5-9 projectile of the present invention on the target. DETAILED DESCRIPTION

[0043] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0044] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0045] A tungsten alloy with excellent armor-piercing performance is prepared from the following raw materials, calculated by mass percentage: 93% W powder (particle size 1-2 μm), 3-4.8% Ni powder, 1-2% Fe powder (particle size 2-5 μm), 0.8-1.5% Co powder (particle size 1-2 μm), 0.3-1.0% silicon dioxide powder (particle size 2-5 μm), 0.1-0.3% Y, and the remainder is inevitable impurities, which totals 100%.

[0046] Further, some reference alloy formulations are shown in Table 1.

[0047] Table 1 Partial reference formula (mass percentage)

[0048]

[0049]

[0050] Furthermore, the preparation process of the tungsten alloy with excellent armor-piercing performance of the present invention comprises the following steps:

[0051] S1. Raw material mixing

[0052] 93wt% W powder (1-2μm), 3-5wt% Ni powder (carbonyl), 1-2wt% Fe (2-5μm), 0.8-1.5wt% Co powder (1-2μm), 0.3-1.0wt% silicon dioxide powder (2-5μm, silicon dioxide powder can be replaced by silicate) are added into a ball milling cylinder with an inner wall of a cemented carbide, alcohol is used as a medium, the amount of paraffin added is 2wt% (total weight of the powder), a cemented carbide ball is used as a grinding ball, the ball-to-material ratio is 3.5:1, ball milling is performed, the ball milling time is 60-72h, after the ball milling is completed, it is sieved through a -350 mesh screen, filtered after settling for 24h, and then dried according to a conventional process to obtain a rubber-doped material;

[0053] S2. Add Y

[0054] The above-mentioned glue-doped material is poured into a V-type mixer, and a complex complex salt ([Y(NH3)4](OH)2)) solution of metal yttrium is added at a ratio of 0.1-0.3wt%Y (net mass), and then the V-type mixer is evacuated, and the evacuation is stopped when the vacuum reaches 100-200Pa, and a sufficient amount of Ar protective gas is injected into the V-type mixer, and the gas pressure is about 1MPa, and then the mixture is rotated and mixed, and placed in a microwave-ultrasonic composite field for microwave-ultrasonic coordinated treatment, and the mixing time is 12-24h. After the mixing is completed, it is cooled for 24h, and then the mixer is opened for unloading to obtain a primary mixture;

[0055] S3, pressing and sintering

[0056] The primary mixture is pressed at a pressure of 4-5 MPa and a holding time of 15-30 seconds. The pressed sample blank is placed in a molybdenum boat with alumina powder (≤200 mesh, the same below) as the bottom, and then covered with a 3-5 mm thick layer of alumina powder. Then, it is pushed into a muffle furnace protected by H2 atmosphere for one-time sintering. The sintering process is as follows: the sample dewaxing time is 3-4 hours, the sintering temperature is 1460-1500°C, the high temperature sintering time is 1.5-2.0 hours, and the sample is sandblasted after sintering out of the furnace;

[0057] S4, vacuum tempering, hot rotary forging and multiple heat treatment

[0058] The sintered and sandblasted samples are put into a vacuum furnace again for high-temperature tempering and vacuum dehydrogenation, the boat is a corundum plate, the high-temperature dehydrogenation and tempering temperature is 1100-1200°C, the holding time is 2h, and the vacuum degree is 0.05-0.1Pa; then the dehydrogenation and tempering samples are hot forged, the forging temperature is 900-1000°C, N2 atmosphere protection, and the radial size deformation after forging is 20-30%; then the forged samples are vacuum heat treated, the heat treatment is repeated 3-4 times, and the quenching temperature is gradually increased each time; the process is as follows: the vacuum degree is 5-10Pa, the temperature is 1050-1300°C, the holding time is 1.5-2h, water quenching (adding 3-5wt% glucose solution), and no tempering after quenching.

[0059] In order to better implement the present invention, alloy formulations of some test examples and comparative examples are listed below.

[0060] Table 2 Part of tungsten alloy formula (mass percentage, W, Ni, Fe, Co content is the same)

[0061] project <![CDATA[Si (calculated as SiO2)]]> Y Test Example 1 0.3 0.1 Test Example 2 0.6 0.3 Test Example 3 1.0 0.3 Comparative Example 1 1.3 0 Comparative Example 2 0 0.3

[0062] In order to better explain the present invention, according to the above preparation process, test examples 1-3 (TA93W, TB93W, TC93W) and comparative examples 1-2 (DA93W, DB93W) samples were prepared with reference to the same process, and at the same time, the conventional high-strength and high-toughness 93W alloy was benchmarked. The samples were processed and tested according to the sample sizes required for the physical property test of conventional metal materials, and the static physical property test results in Table 3 were obtained.

[0063] Table 3 Test results of static physical properties of test examples and comparative examples

[0064]

[0065] The tensile strength test diagram of high strength and high toughness 93W alloy is shown in Figure 2 Its metallographic image (×160) and backscattered electron image (×300) are as follows Figure 8 and Fig. 9 As shown in Table 3, Figure 2 , Figure 8 and Fig. 9 It can be seen that the bonding phases of the conventional high-strength and high-toughness 93W alloy are nickel, iron and cobalt. It exhibits high tensile strength. There is a large gap between the yield strength and the tensile strength. The material has excellent impact toughness, high elongation after fracture, and the density and hardness are within the normal range.

[0066] The tensile strength test diagram of TA93W alloy of Test Example 1 of the present invention is shown in Figure 3 and Figure 4 Its metallographic image (×200) and backscattered electron image (×300) are as follows Fig.10 and Fig.11 As shown in Table 3, Figure 3 , Figure 4 , Fig.10 and Fig.11 It can be seen that the bonding phases of TA93W alloy are nickel, iron and cobalt. Compared with the high-strength and high-toughness 93W alloy, after adding 0.3% SiO2 and 0.1% Y, the tensile strength shows a downward trend, the gap between yield strength and tensile strength decreases, the impact toughness and elongation of the material both decrease slightly, and the density and hardness are within the normal range.

[0067] The tensile strength test diagram of TB93W alloy of Test Example 2 of the present invention is shown in Figure 5 Its metallographic image (×160) and backscattered electron image (×200) are as follows Fig.12 and Fig.13 As shown in Table 3, Figure 5 , Fig.12 and Fig.13 It can be seen that the bonding phases of TB93W alloy are nickel, iron and cobalt. Compared with the high-strength and high-toughness 93W alloy, after adding 0.6% SiO2 and 0.3% Y, the tensile strength of TB93W alloy remains unchanged, the gap between yield strength and tensile strength almost disappears, the impact toughness and elongation of the material are significantly reduced, the material density is significantly reduced, and the hardness is within the normal range.

[0068] The tensile strength test diagram of TC93W alloy of Test Example 3 of the present invention is shown in Figure 6 and Figure 7 Its metallographic image (×200) and backscattered electron image (×1500) are as follows Fig.14 and Fig.15 As shown in Table 3, Figure 6 , Figure 7 , Fig.12 and Fig.13 It can be seen that the bonding phases of TC93W alloy are nickel, iron and cobalt. Compared with the high-strength and high-toughness 93W alloy, after adding 1.0% SiO2 and 0.3% Y, the tensile strength of TC93W alloy is significantly improved, the material does not show yield phenomenon, and presents obvious shear strain and brittle fracture characteristics. The impact toughness and elongation after fracture of the material are significantly reduced, the material density is significantly reduced, and the hardness is within the normal range.

[0069] According to the above test results, it can be found that the tensile strength of conventional high-strength and high-toughness 93W alloy reaches 1200-1235Rm / MPa and the impact toughness is as high as 130J / cm 2 The elongation after fracture is between 13.5-15.0, the hardness (HRC)>40, and the density is 17.53-17.60g / cm 3When 0.3% SiO2 and 0.1% Y are added, the performance of TA93W alloy is significantly affected: the tensile strength is reduced to 1120-1170Rm / MPa, the decrease is close to 10%, and the impact toughness is reduced to 65-77J / cm 2 The elongation after fracture is reduced to between 9.0-13.0, with a decrease of 20-30%; the hardness (HRC) is around 40, with no obvious change, and the density is 17.30-17.45g / cm 3 , slightly decreased; comprehensive analysis shows that the addition of silicon oxide and Y has a dramatic effect on the performance of TA93W, which is consistent with the conclusion of the effect of adding rare earth oxides on the performance of tungsten alloys in China. However, with the increase of the addition amount, when 0.6% SiO2 and 0.3% Y are added, the effect on the performance of TB93W alloy has undergone a dramatic evolution. Compared with the conventional high-strength and high-toughness 93W alloy: the tensile strength has risen to 1200-1230Rm / MPa, with almost no change, and the impact toughness has dropped to 58-61J / cm 2 The elongation after fracture is reduced to between 8.0-10.0, with a decrease of 35-40%; the hardness (HRC) is around 40, with no obvious change, and the density is between 17.14-17.20g / cm 3 , and continued to decline. With the continued increase in the amount of addition: 1.0% SiO2, 0.3% Y, the influence on the performance of TC93W alloy is further manifested. While the material has high strength, it also shows sensitive shear strain characteristics: the tensile strength rises to 1340-1410Rm / MPa, the increase is close to 10%, and the impact toughness decreases to 41-43J / cm 2 , the decline reached 80%, the elongation after fracture decreased to between 5.0-7.0, the decline reached 60-70%; the hardness (HRC) was around 40, with no significant change, and the density was 17.02-17.06g / cm 3 , the decline is about 3%, which has a huge impact. By observing the organizational structure of the above samples, it can be found that the addition of silicon oxide and Y, combined with the preparation process of the present invention, has a great impact on the microstructure of the tungsten alloy sample:

[0070] ① The preparation process of the present invention makes the silicon oxide grains and the formed rare earth oxide grains obviously and evenly distributed between the tungsten grains and the bonding phase, or exist in the bonding phase, giving full play to the effects of dispersion strengthening, solid solution strengthening and precipitation strengthening; at the same time, the diffusion of tungsten into the bonding phase is reduced, the growth of tungsten grains during the sintering process is effectively suppressed, and the grains are refined, thereby greatly improving the strength of the alloy. After the multiple thermal treatments of the present invention, the tensile strength is increased by 10% compared with the conventional high-strength and high-toughness 93W alloy;

[0071] ② The added silicon oxide grains and the formed Y oxide grains are distributed between the tungsten grains and the bonding phase, or exist in the bonding phase, which greatly enhances the shear strain characteristics of the 93W alloy; as the addition amount reaches: 1.0% SiO2 (starting to change significantly between 0.6-1.0%), 0.3% Y, the shear strain sensitivity of the material is fully manifested, and the impact toughness is reduced to 41-43J / cm compared with the conventional high-strength and high-toughness 93W alloy 2 The elongation after break is reduced to between 5.0-7.0, with a decrease of 60-70%;

[0072] ③ The enhancement of the shear strain characteristics of the material by adding silicon oxide grains and forming Y oxide grains is very specific in the material tensile strength test diagram. Figure 2 In the conventional high-strength and high-toughness 93W alloy material, as the tensile force increases, the material strength reaches the yield strength of 1196Rp0.2 / MPa, and the material undergoes strong plastic deformation, and severe tearing occurs between the tungsten grains and the bonding phase, and within the bonding phase itself. The tensile strength of the material is further improved, and the elongation reaches 13.5% and finally reaches the fracture limit, that is, the tensile strength reaches 1235Rm / MPa. From yield to fracture, the strength increases by 3.26%. Figure 3 , Figure 4 In the test, as the tensile force of TA93W alloy material increases, after the material strength reaches the yield strength of 1150 and 1170Rm / MPa, the material undergoes certain plastic deformation, and cracks are generated between silicon oxide grains and tungsten grains, and extend between the bonding phase and the oxide grains. There is no tearing inside the bonding phase itself. After the elongation reaches 9.0%, it finally reaches the fracture limit, that is, the material fractures after the tensile strength reaches 1156 and 1171Rm / MPa. From yield to fracture, the tensile strength hardly changes.

[0073] ④In Figure 5In the experiment, because 0.6% SiO2 and 0.3% Y were added to the TB93W alloy material, a large number of oxide heterogeneous phases appeared in the alloy structure, which played the role of dispersion strengthening, solid solution strengthening and precipitation strengthening on the one hand; on the other hand, a large number of oxide heterogeneous phases existed around the tungsten grains and inside the bonding phase, forming a large number of crack sources and expansion channels; therefore, with the increase of tension, the material strength reached the yield strength of 1223Rm / MPa, the material produced a little plastic deformation, cracks were generated between silicon oxide grains and tungsten grains, and extended between the bonding phase and the oxide grains, and almost no tearing was generated inside the bonding phase itself. After the elongation reached 8.0-10.0%, it finally reached the fracture limit, that is, the material fractured after the tensile strength reached 1227Rm / MPa, and the tensile strength hardly changed from yield to fracture; the alloy material showed very sensitive shear strain characteristics;

[0074] ⑤In Figure 5 In the present invention, the shear strain characteristics of the TC93W alloy material are more prominent: the alloy material is added with 1.0% SiO2 and 0.3% Y, and the oxide heterogeneous phase in the alloy structure is more abundant, so when the alloy is subjected to deformation and yielding, the dispersion strengthening, solid solution strengthening and precipitation strengthening of the oxide heterogeneous phase are more prominent. When the yield strength reaches 1322 / 1362Rp0.2 / MPa, the TC93W alloy hardly produces plastic deformation; although the oxide heterogeneous phase exists around the tungsten grains and inside the bonding phase, forming a large number of crack sources and expansion channels, the "pinning" of the oxide heterogeneous phase in the bonding phase hinders and delays the rapid expansion of the crack, thereby resulting in the appearance of higher tensile strength, which is nearly 20Rm / MPa higher than the yield strength. The TC93W alloy material prepared by the present invention not only has good high-strength characteristics, but also has excellent shear strain characteristics;

[0075] Correspondingly, according to the above test method, it can be seen from Table 3 that when the silicon oxide exceeds the range specified in the present invention and Y is not added, the strength of the tungsten alloy decreases, especially the toughness decreases significantly. This shows that the addition amount of silicon oxide should not exceed the range specified in the present invention, otherwise the mechanical properties of the material will be affected due to excessive silicon content; when only Y is added, the mechanical properties of the tungsten alloy decrease slightly, indicating that only by refining the grains, the mechanical properties of the tungsten alloy material are limited, and the mechanical properties of the tungsten alloy material are easily reduced.

[0076] Target shooting test

[0077] The conventional high-strength and high-toughness 93W alloy and the TC93W alloy of the present invention are used to process and manufacture 30mm armor-piercing shell cores and normal charges, and 4-5 30mm armor-piercing shell test shells are prepared for standby use. A live-fire target shooting test was conducted at a certain shooting range. The target was a first layer of 20mm thick aluminum alloy plate (38°), 2-7 layers of 5, 2, 2, 5, 2, 5mm thick aluminum alloy plates, and the 8th layer, i.e. the last layer, was a 50mm thick armor steel plate (38°); the ballistic length was 1000m, the initial shooting velocity (m / s) was 1240-1250, and the impact velocity was 980-1050m / s. The target shooting results are shown in Table 4 below. Figure 16-17 The results of the live-fire target shooting test prove that the 30mm armor-piercing projectile made of the T93W alloy prepared by the present invention has a better armor-piercing ability than the armor-piercing projectile made of the conventional high-strength and high-toughness 93W alloy of a domestic large factory. It can penetrate 20mm aluminum alloy plate and 6 layers of 2-5mm aluminum alloy thin plate, and can still penetrate 81mm armor steel plate; while the conventional high-strength and high-toughness 93W alloy can only form a crater on the armor steel plate and fail to penetrate.

[0078] Table 4 Target shooting test results

[0079]

[0080]

[0081] This shows that the good high-strength characteristics and excellent shear strain characteristics of TC93W alloy materials have been verified in live ammunition target shooting: the core prepared by high-strength and high-toughness conventional 93W alloy can not penetrate 50mm thick aluminum alloy plate (inclined 38°) armor plate after 1000m of 30mm armor-piercing shells, and the core prepared by TC93W alloy material can continuously penetrate 50mm thick armor plate (inclined 38°) under the same test conditions; therefore, TC93W alloy material shows better "self-sharpening" and better armor-piercing ability in armor-piercing. Accordingly, DA93W alloy and DB93W alloy were prepared into armor-piercing shells for target shooting tests. The experimental results are similar to those of conventional high-strength and high-toughness 93W alloys, which can only form craters on armor plates and fail to penetrate armor plates.

[0082] It is worth noting that the adiabatic shear band (ASB) is actually a narrow band region with highly localized shear deformation, with a width of generally 1-102 μm. Shear strains of the order of 101-102 can be generated in the ASB, and the strain rate can be as high as 105-107 s -1, the temperature rise can reach 102-103K. The so-called "adiabatic" is actually an approximate statement. Due to the high-speed deformation of the material and the short deformation process, in such a short time, most (about 90%) of the plastic work is converted into heat and has no time to dissipate, so it is approximately considered that the deformation process at such a high strain rate is an adiabatic process. Adiabatic shear is an important phenomenon of materials under impact loads. It is a unique local instability phenomenon. It is closely related to material failure. The occurrence of ASB in material components means the decrease or loss of the material's bearing capacity, which is considered to be a precursor to material failure. For example, for armor materials, adiabatic shear is one of its main failure forms. When manufacturing materials for kinetic energy armor-piercing projectiles, strong shear instability and deformation localization sensitivity are required, so that "self-sharpening" occurs during armor-piercing and penetration. Previously, it was believed that powder metallurgy tungsten-based alloys were very insensitive to adiabatic shear; however, recent studies have found that the adiabatic shear insensitivity of tungsten-based alloys is relative: on the one hand, the microstructure of the material (such as the shape and spatial orientation of tungsten particles) has an important influence on the deformation, destruction and deformation localization mechanism of the material. If the direction of the maximum shear stress is consistent with the orientation of the tungsten particles, the failure is the result of the combined action of several destruction mechanisms such as brittle fracture of tungsten particles, destruction of the bonding phase, separation of tungsten-tungsten interface and separation of tungsten-bonding phase interface; if the direction of the maximum shear stress and the orientation of the initial tungsten particles have a large angle, the tungsten particles will be adiabatic shear deformation localized, and the violent deformation and destruction of tungsten particles at this time is the main mechanism of failure of tungsten alloys. On the other hand, the stress state also has a certain influence on the deformation of the material. Under one-dimensional stress impact conditions (high strain rate, large strain), tungsten alloys are uniformly deformed, and it is difficult to observe the appearance of microcracks, microvoids and adiabatic shear bands; in dumbbell-shaped and stepped cylindrical specimens, adiabatic shear bands will appear at stress concentrations even at very low impact strengths, and stress distribution has an important influence on the formation of adiabatic shear bands. The thin section of the dumbbell-shaped specimen is constrained at both ends, so the shear band is not easy to expand and it is difficult to cause the overall destruction of the specimen. However, in the step-shaped specimen, the shear band is constrained on one side and is easy to expand, eventually leading to the overall fracture of the specimen. The crack originates from the shear band and develops along it.

[0083] Furthermore, in order to verify the effect of the multiple heat treatment process of the present invention, the TC93W alloy material of the present invention was used as the test object, and the existing preparation process was adopted, that is, alloy powder mixing + pressing molding + hydrogen sintering + hot forging + annealing process was adopted, and the multiple heat treatment process in the preparation process of the present invention was replaced by an annealing process to prepare the TC93W-T alloy. The TC93W-T alloy was prepared into a discarding sabot armor-piercing projectile for target shooting test. The experimental results were: the 1st to 7th layers were penetrated, the 3rd round hit the edge of the target, and the target was slipped; the 1st, 2nd, and 4th rounds hit the target and formed a crater. It can be seen that the TC93W-T alloy can only form a crater on the armored steel plate, and failed to penetrate the armored steel plate.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A tungsten alloy with excellent armor-piercing performance, characterized in that: The tungsten alloy is prepared from the following raw materials by mass percentage: 93% W powder, 3-4.8% Ni powder, 1-2% Fe powder, 0.8-1.5% Co powder, 1.0% SiO2 powder, 0.3% Y, and the remainder is inevitable impurities, which totals 100%. The preparation method includes the following steps: A. Preparation of mixed materials: Add W powder, Ni powder, Fe powder, Co powder and SiO2 powder into a ball mill, sieve after ball milling, and then filter and dry to obtain a rubber-doped material; B. Mixing the rubber-doped material and the yttrium complex salt solution in a mixer, evacuating the mixer, injecting a protective gas into the mixer, and then rotating and mixing, and placing the mixture in a microwave-ultrasonic composite field for microwave-ultrasonic coordinated treatment, and discharging the mixture after the mixing is completed to obtain a primary mixture; C. Pressing and sintering: the primary mixture is pressed and formed to obtain a sample blank, the sample blank is loaded into a molybdenum boat, and a one-time sintering is performed in a muffle furnace in a H2 atmosphere, and the obtained sample is sandblasted; D. Vacuum tempering, hot rotary forging and multiple heat treatments. The sintered and sandblasted samples are placed in a vacuum furnace for high-temperature tempering and vacuum dehydrogenation. The samples are then hot rotary forged. The forged samples are subjected to multiple vacuum heat treatments. The heat treatment is repeated 3-4 times. The quenching temperature is gradually increased each time. No tempering is performed after quenching.

2. The tungsten alloy with excellent armor-piercing performance as claimed in claim 1, characterized in that: The particle size of the W powder is 1-2 μm, the particle size of the Fe powder is 2-5 μm, the particle size of the Co powder is 1-2 μm, and the particle size of the SiO2 powder is 2-5 μm.

3. The tungsten alloy with excellent armor-piercing performance as claimed in claim 1, characterized in that: The SiO2 powder is prepared from silicate powder; the raw material metal yttrium is provided by yttrium complex salt solution.

4. The tungsten alloy with excellent armor-piercing performance as claimed in claim 1, characterized in that: In step C, the sintering process is as follows: the sample dewaxing time is 3-4 hours, the sintering temperature is 1460-1500° C., and the high-temperature sintering time is 1.5-2.0 hours.

5. The tungsten alloy with excellent armor-piercing performance as claimed in claim 1, characterized in that: In step D, the high-temperature dehydrogenation and tempering temperature is 1100-1200°C, the holding time is 2h, and the vacuum degree is 0.05-0.1Pa; the hot rotary forging temperature is 900-1000°C, and it is carried out under the protection of N2 atmosphere, and the radial dimension deformation after rotary forging is 20-30%.

6. The tungsten alloy with excellent armor-piercing performance as claimed in claim 1, characterized in that: In step D, the vacuum heat treatment process parameters are: vacuum degree of 5-10Pa, temperature of 1050-1300°C, holding time of 1.5-2h, and water quenching.

7. Application of tungsten alloy with excellent armor-piercing performance in military equipment, characterized in that: The tungsten alloy is used as a raw material for preparing armor-piercing bullets, wherein the tungsten alloy is the tungsten alloy with excellent armor-piercing performance as described in any one of claims 1-6.

Citation Information

Patent Citations

  • High specific gravity tungsten alloy material and preparation method for nano crystal block thereof

    CN101148725A

  • Tungsten alloy and preparation method thereof

    CN111057926A

  • Tungsten alloy with weak low-temperature brittleness and preparation method and application thereof

    CN117947300A